Covid-19 Pandemic Situation In The Arab World Till June 11, 2020: Spatial Panorama Obtained Following The Response Plan Implemented - Fatine Hadrya; Faiçal El Hattimy; Hind Hami; Abdelrhani Mokhtari; Abdelmajid Soulaymani (European Scientific Journal, ESJ, 2021)
Background: The COVID-19 pandemic is a global health emergency of this century. The Arab region is not spared from this scourge. This paper focuses on describing the current epidemiological situation of Coronavirus Disease 2019 (COVID-19) in the Arab world, as of June 11, 2020. Methods: An observational study of all laboratory-confirmed cases of COVID-19, reported in each Arab country since the appearance of the first case until June 11, 2020, was carried out. Results: Twenty-two Arab countries have reported a total of 398,954 confirmed cases of COVID-19 and 5,241 deaths, with a cumulative incidence of 950 cases per 1,000,000 population and a cumulative mortality rate of 13 deaths per 1,000,000 population. Of all recorded cases, 240,137 (60.19%) have recovered from COVID-19. The highest incidence rate of COVID-19 was observed in Qatar (26,988 cases per 1,000,000 population) and the lowest incidence was recorded in Libya (59 cases), Yemen (21 cases), and Syria (10 cases). Kuwait had the highest mortality rate for COVID-19 (67 deaths per 1,000,000 population). Eight countries had a case fatality rate (CFR) less than 1% (e.g., Bahrain, Oman and Qatar). The highest CFR was observed in Yemen (23.01%). Only three countries were ranked first in terms of remission (Morocco, Palestine and Tunisia). The rate of remission did not exceed 20% in Libya, Mauritania, and Yemen. Conclusion: Some countries were more affected than others in terms of morbidity and mortality. The success of a national response plan against COVID-19 is closely linked to the devotion of health professionals and community engagement.